Evaluation of Impacts of Cellular Metabolism on the Migration of Ovarian Cancer Cells by Two in Vitro Assays: A Method Comparison Study: - Salami, Siamak; Ghahremani, Hossein; Sirati-Sabet, Majid (Galen Medical Journal, 2020)
Background: Alteration of metabolic pathways in cancer cells can intensely modulate their migration as an important step in invasion and metastasis. Ketogenic diet showed some contradictory results in cancer patients. In this study the impact of metabolic reprogramming of A2780CP as a model of ovarian cancer stem-like cells on cell migration by two in vitro methods: wound healing and soft agar colony-forming assays. Materials and Methods: short term and long term metabolic reprogramming were done by restriction of glucose to 250mg/L with or without enrichment with beta-hydroxybutyrate (5 milimolar) for 48 hours and 30 days, respectively. Wound healing assay was done and the wound ratio was calculated for 24 and 48 hours. Soft agar colony formation assay was also done in treated and control cells. For method comparison, ten biological replicates were analyzed in triplicate. Results: Migration of A2780CP ovarian cancer stem-like cells were significantly alleviated by long term glucose restriction but no significant changes were observed in short term study. Beta-hydroxybutyrate enrichment did not produce significant impacts on glucose restriction in short or long term studies. Conclusion: The results of colony formation in soft agar and wound or scratch healing assay were in good correlation and convergence which could be used interchangeably in the investigation of metabolic reprogramming in cancer cells. [GMJ.2020;9:e1831]